Clinical, demographic and histopathological features of symmetrical acral keratoderma. (April 2014) - Li, C.‐X.; Han, C.‐L.; Zeng, K.; Zhang, X.‐B.; Ma, Z.‐L.
Summary Background A series of cases of symmetrical acral keratoderma have been described recently in China. However, no studies about its demographic information and epidermal barrier function have been documented. Objectives To describe the clinical manifestation, demographic information and clinicopathological features of 71 cases with symmetrical acral keratoderma. Patients and methods Seventy‐one cases with symmetrical acral keratoderma were retrospectively reviewed. Their demographic information, clinical manifestations, histopathology and epidermal barrier function were analysed. Results Among these patients, there were 64 males and seven females, ranging in age from 4 to 53 years with an average age at onset of 27 ± 8·9 years. Clinical manifestation was characterized by brown hyperkeratotic patches over the dorsum of the hands, palms and feet, dorsal digits and wrists, elbows, knees and ankles. The lesions became dramatically whitish with mild swelling immediately after soaking in water and resolved spontaneously in winter. In patients, a moderate increase of transepidermal water loss (TEWL) from 16·16 ± 6·15 to 9·9 ± 4·21 g m−2 h−1 (P = 0·0054) and a moderate decrease of skin hydration from 65·9 ± 5·06 to 42·58 ± 10·73 (P < 0·01) in comparison with the control group were observed. Histopathological examination revealed epidermal hyperkeratosis, acanthosis and papillomatous hyperplasia as well as dermal infiltration with a few lymphocytes. Conclusions Symmetrical acral keratoderma is characterized by symmetry, acra, keratinization and marked seasonal changes. The epidermal barrier function of the skin was negatively affected.